Mergers and acquisitions : the case of Microsoft Corporation and Activision Blizzard Inc. - Stenmark, Robert Vicent Leon (2013)
Globalization, geographic diversification and deregulation of markets have led to an increasingly competitive environment for most companies. Increasing competition often leads to higher efforts to persuade consumers to by the given company’s product, and consequently margins are affected. Moreover, this development of the business environment also faces as a threat to most companies’ organic growth. For this reason, companies often envision mergers and acquisitions as a solution to this problem. The decision of taking on a larger transaction to acquire another company is often motivated by the fact that it may create additional opportunities for the company, enable higher growth, and ultimately create shareholder value. Mergers and acquisitions are especially apparent in industries that are highly affected technological innovations. The rationale for this is grounded in the potential target company’s technological assets or specific capabilities, which may pose as highly valuable for the acquirer. The acquisition of the target company enables the transfer of these skills and may create a competitive advantage, which in turn creates a driver for long-term sustainable growth. This paper will analyze the possibility of creating additional value through mergers and acquisition. The paper will start of by surveying literature on various theories on valuation of companies. This part will also present evidence on what valuation techniques that proves to yield reliable results, and discuss value creation in the light of mergers and acquisitions. In the second part the paper the presented theory will be put into practice by through a proposed M&A-situation between Microsoft Corporation and Activision Blizzard, Inc. This part will present a thorough companyand industry analysis that will provide the basis for a valuation of the companies, both on a standalone basis and on a consolidated basis. The final part of the paper will present the acquisition process itself, and discuss issues that are related to the acquisition. This part will also present the optimal way for Microsoft to proceed in acquiring Activision Blizzard. When valuing the companies individually, both companies show indications of being undervalued compared to their average market values for the last year. Microsoft value is displaying signs of being overly undervalued, while Activision Blizzard only is slightly undervalued. A valuation of the combined company reveals that there were considerable opportunities for additional value creation through a merger. Finally, based on the analysis and the valuations in the paper suggests that that Microsoft should proceed with the acquisition. The acquisition will be presented to Activision Blizzard’s shareholders as a friendly tender offer, in order to persuade them to sell their shares in the company. The price offered for the outstanding shares of the company is suggested to provide current shareholders with a premium of 29.4% to the average market capitalization of the company. Moreover, the acquisition will be financed with a cash-only transaction, as to maintain financial flexibility and in line with Microsoft’s acquisition history.